(untitled) (AYUSHDHARA, 2021)
Curcuma longa Linn. is a very commonly used herb in the day-to-day life for therapeutic and culinary purposes. Haridra commonly known as ‘Golden spice’ belongs to Zingiberaceae family and is very well known for its pharmacological actions like hepatoprotective, anti-allergic, immune-stimulant, anti-cancer, anti-tumor, anti-hyperlipidemic, anti-oxidant, anti-microbial, anti-diabetic etc. According to the growing regions there are so many varieties of Haridra like Kerala, Tamil Nadu, Maharashtra, Andhra Pradesh, Orissa and North Eastern varieties. All medicinal plants contain phytochemicals or bioactive compounds which plays the key role in its therapeutic action. Most of the drugs show variations in these phytochemicals due to its growing regions which results in severe variations of its quality and efficacy. Also the globalisation and increasing demand for Ayurveda drugs resulted in unavailability of authentic and quality drugs in market which meets the quality standards. Objective: Kerala variety of Turmeric is very well known for its high Curcumin, which is up to 6.5%. Present study is to evaluate the quality of Kerala variety of Haridra sample. Material and methods: This study involves pharmacognostical and phytochemical analysis of Kerala variety of Haridra samples to ensure its purity, safety and quality. Observations and Results: All the findings of the phytochemical and pharmacognostical study were within the standards of quality as per API. Conclusion: The present sample of Haridra, the Kerala variety was found to be rich in Quality and was safe, pure and authentic.